2006
DOI: 10.1038/sj.onc.1209718
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cyclin B1 and CDK activity during apoptosis induced by camptothecin treatment

Abstract: We have studied the role of cyclins and cyclin-dependent kinase (CDK) activity in apoptosis induced by camptothecin (CPT). In this model, 22% of the cells stain for annexin-V at 24 h and then proceed to be 93% positive by 72 h. This time window permits the analysis of cyclins in cells that are committed to apoptosis but not yet dead. We provide evidence that cyclin protein levels and then associated kinase levels increase after CPT treatment. Strikingly, cyclin B1 and cyclin E1 proteins are present at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Intriguingly, S181A tumors showed higher cyclin B1 expression than the others (Fig. 1D) in line with the requirement of increased cyclin B1 for apoptosis induction previously reported in several tumor cell lines (17)(18)(19). Moreover, cyclin B1 overexpression has already been related to the mild transforming phenotype of codon 13 KRAS mutations in NIH3T3 models (16).…”
Section: Resultssupporting
confidence: 65%
“…Intriguingly, S181A tumors showed higher cyclin B1 expression than the others (Fig. 1D) in line with the requirement of increased cyclin B1 for apoptosis induction previously reported in several tumor cell lines (17)(18)(19). Moreover, cyclin B1 overexpression has already been related to the mild transforming phenotype of codon 13 KRAS mutations in NIH3T3 models (16).…”
Section: Resultssupporting
confidence: 65%
“…This was accompanied by an increase in the expression of cyclin B1 and cyclin E2 in these cells. siRNA-mediated inhibition of cyclin B1 prevented the cells from undergoing apoptosis, whereas siRNA-targeting of cyclin E2 had no effect (Borgne et al, 2006). Thus, cyclin B1 expression is required for apoptotic induction by camptothecin in HT29 cells.…”
Section: Pro-and Anti-apoptotic Effects Of Cyclinsmentioning
confidence: 89%
“…Interestingly, targeting of cyclin B1 by siRNA in primary human vascular endothelial cells (HUVECS), does not decrease their proliferation . Camptothecin treatment of HT29 cells induced apoptosis (Banerji and Los, 2006;Borgne et al, 2006;Huang et al, 2006). This was accompanied by an increase in the expression of cyclin B1 and cyclin E2 in these cells.…”
Section: Pro-and Anti-apoptotic Effects Of Cyclinsmentioning
confidence: 96%
“…In accord with that, it has been shown that nuclear accumulation of cyclin B1 is one of the factors involved in triggering this kind of cell death, as it was found mainly in the cytoplasm of the cells that were apoptotic-resistant and accumulated in the nucleus of the apoptotic-prone ones [27]. Moreover, it has been proven that targeting cyclin B1 protein by RNAi or chemical inhibitors leads to decreased number of apoptotic HT29 cells after treatment with camptothecin [23]. On the other hand, reduction of cyclin B1 level may also induce cell cycle arrest and apoptosis in some cancer cells [28].…”
Section: Discussionmentioning
confidence: 59%
“…One of the causes of mitotic catastrophe execution may be premature entry into mitosis before the completion of DNA replication, which results in abnormal organization of chromosomes in the presence of the high activity of cyclin B1/Cdk1 complex in the nucleus area [11,23]. There are suggestions that such an aberrant mitosis is mediated by Notch inhibition followed by NF-kB activity, which in turn induces high levels of cyclin B1 [24].…”
Section: Discussionmentioning
confidence: 99%